Implementasi Aviation Safety Improvement oleh Pemerintah Indonesia-Australia melalui Kerjasama Air Transport Sector - Laksmi Pradnyakumari, Ni Made Ratih; Fasisaka, Idin; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
ABSTRACT Indonesia is Australia’s closest neighbor countries are cooperating in various fields including the field of aviation. Australia has a strong aviation company and contribute to the advancement of the world’s airlines to join the international civil aviation organization (ICAO) and helped develop the company’s low in many countries, especially in Asia Pacific. The Aviation sector included into one of the most important area, because of the creation of air traffic for people’s mobilization especially tourists who produce the country’s foreign exchange. The implementation of aviation safety improvement is done through the cooperation of the air transport sector in which inside it there are grains of technical implementation carried out by both countries, and also implementation support in such cooperation namely Indonesia Australia Aviation Security Project (IAAP), Indonesia-Australia Direct Flight Cooperation, and Indonesia Transport Safety Assistance Package (ITSAP). The implementation is a form of political negotiation within the framework of relations between the two countries to persue their own national interests. This study assessed using two concepts that is sustainable development of air transport and geostrategic concept. The Locus of this study is from 2008-2013. Keywords : air transport, aviation safety improvement, air transport cooperation